2012
DOI: 10.1177/0194599812466055
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparities in Scholarly Productivity within Academic Otolaryngology Departments

Abstract: Objective. To examine whether there are gender disparities in scholarly productivity within academic otolaryngology departments, as measured by academic rank and the h-index, a published, objective measure of research contributions that quantifies the number and significance of papers published by a given author.Study Design and Setting. Analysis of bibliometric data of academic otolaryngologists.Methods. Faculty listings from academic otolaryngology departments were used to determine academic rank and gender.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
215
5
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(232 citation statements)
references
References 58 publications
(177 reference statements)
9
215
5
3
Order By: Relevance
“…Results show this had no influence on success. This is consistent with studies done for the orthopedic surgery, otolaryngology, and ophthalmology departments [6,8,17]. These studies likewise found that the mean H-index of NIH-funded faculty whose terminal degree was an MD (or MD equivalent) was not statistically different than colleagues with PhDs or both MD and PhD degrees.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Results show this had no influence on success. This is consistent with studies done for the orthopedic surgery, otolaryngology, and ophthalmology departments [6,8,17]. These studies likewise found that the mean H-index of NIH-funded faculty whose terminal degree was an MD (or MD equivalent) was not statistically different than colleagues with PhDs or both MD and PhD degrees.…”
Section: Discussionsupporting
confidence: 89%
“…Further doi: 10.15761/GOD.1000181 Volume 3 (3): 311-314 difficult time training and recruiting females [6]. Despite the more equal representation of females and males in dermatology, the number of females who receive NIH funding is far less.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These issues and other potential limitations of the h index have been widely reported in the literature. 3,7,9,10,[12][13][14][15]18,23,25,26,[28][29][30]35,[39][40][41] Despite these known limitations, the h index is an objective measure that takes into account the frequency with which a faculty member has had an impact upon scholarly discourse within a field and has been shown in many analyses to have a strong association with academic promotion, receiving external funding, graduate medical education, and a variety of other factors measuring achievement.…”
Section: Discussionmentioning
confidence: 99%
“…The h index is a bibliometric whose use has been previously described among academic physicians in neurological surgery as well as in other specialties. 6,7,9,10,12,21,[23][24][25][26][27]29,31,32,[35][36][37][38][39][40] It has been shown to have a strong association with scholarly impact, academic advancement, National Institutes of Health (NIH) funding procurement, and other measures of scholarly productivity. It is a widely accessible and easily calculable measure that indicates the degree to which an author is frequently cited on a regular basis, throughout his or her body of work (rather than disproportionate citation of a single work).…”
mentioning
confidence: 99%